2019
DOI: 10.1029/2019sw002271
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Machine Learning and Feature Selection Techniques for Prediction of the Kp Index

Abstract: The Kp index is a measure of the midlatitude global geomagnetic activity and represents short‐term magnetic variations driven by solar wind plasma and interplanetary magnetic field. The Kp index is one of the most widely used indicators for space weather alerts and serves as input to various models, such as for the thermosphere and the radiation belts. It is therefore crucial to predict the Kp index accurately. Previous work in this area has mostly employed artificial neural networks to nowcast Kp, based their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…We have further demonstrated that including a simple, operationally-available proxy for the likelihood of solar activity improves the prediction of geomagnetic storms. The inability of K p prediction models to predict larger storms (K p ≥ 5) well from L1 solar wind data has previously been discussed in the literature (see, e.g., Zhelavskaya et al, 2019), and this work shows that including solar X-ray flux can directly improve the prediction of high levels of geomagnetic activity. In this work we found that including solar X-ray flux in our model features reduces the overall RMSE by 0.01, from 0.78 to 0.77.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We have further demonstrated that including a simple, operationally-available proxy for the likelihood of solar activity improves the prediction of geomagnetic storms. The inability of K p prediction models to predict larger storms (K p ≥ 5) well from L1 solar wind data has previously been discussed in the literature (see, e.g., Zhelavskaya et al, 2019), and this work shows that including solar X-ray flux can directly improve the prediction of high levels of geomagnetic activity. In this work we found that including solar X-ray flux in our model features reduces the overall RMSE by 0.01, from 0.78 to 0.77.…”
Section: Discussionmentioning
confidence: 61%
“…Capturing uncertainty, providing probabilistic predictions and improving our ability to capture transient behavior are all within reach with modern tools and do not require sacrificing model predictive performance. We hope that future work continues to bring together recent advances in feature selection (e.g., Zhelavskaya et al, 2019), model design to accommodate probabilistic prediction, and more complex solar data sources such as solar magnetograms, to provide accurate forecasting of strong geomagnetic activity with longer lead times. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While tests of Shprits et al (2019) provided a systematic error estimation for the models based on neural networks, it remained unclear if the accuracy could further be improved by utilizing different methods for regression. To address this question, Zhelavskaya et al (2019) compared the performance of a number of machine learning (ML) methods for predicting the Kp index. In particular, they used Linear Regression (LR), Gradient Boosting (GB) (e.g.…”
Section: Index Nowcasting and Forecastingmentioning
confidence: 99%
“…MI is a quantity that represents the "amount of information" that can be obtained from one random variable through observation of another random variable. See Figure 1 in Zhelavskaya et al (2019) for further illustration of these methods. The obtained results (Fig.…”
Section: Index Nowcasting and Forecastingmentioning
confidence: 99%